ETHICS MECHANISM OF LEADERSHIP FOR CONFLICT MANAGEMENT IN AN ORGANIZATION - อารักษ์โพชฌงค์, วุฒิชัย; วารีสมบูรณ์, ลักขิกา (RMUTT Global Business and Economics Review, 2018)
The important management organization is to inculcate ethical behavior within the Organization. Which constitute a development of the idea. The subconscious feelings of the members of the organization to have good behavior, according to norms, social values and traditions. Therefore, the development of human resources the moral and ethics. It is directly on the success of the organization in terms of building confidence, dedication, good image and conflict management within the organization. To strengthen ethics in the Organization, is considered a strong cost management or organization leaders can develop guidelines or the application, as appropriate, to the Organization and management of conflict in various ways. In both the prevention and suppression of dimension fortress. The management of conflicts that may be a factor in the organization does not meet the objectives. To cultivating the ethical happening in organization. Necessary leader or leaders must push and a model of ethical principles upheld in practice. This article presents the importance of the ethics Mechanism of leadership or management that is used as an ethics mechanism for conflict management, to achieve the efficiency and sustainability of the organization.